ANALISIS INTRUSI AIR LAUT MEGGUNAKAN DATA RESISTIVITAS DAN GEOKIMIA AIRTANAH DI DATARAN ALUVIAL KOTA SEMARANG - Tabitha Abid Ardaneswari; Tony Yulianto; Thomas Triadi Putranto (Youngster Physics Journal, 2016)
emarang lowland-alluvial area is in the state of salt water intrusion, that has a direct impact to the groundwater quality. Groundwater quality is not only triggered by water level decreasing factors due to the groundwater exploitation,but also by the factor of lithology and aquifer condition. The purpose of this research is to know the resistivity rocks value, the value of groundwater quality, and to analyze the distribution of the estimated area that has been instuited by salt water. The result of processed data with Progress 3.0 is in the form of resistivity value which is correlated with groundwater quality testing value with salinity, electrical conductivity, dissolved oxygen, andpH parameters. Based on the geo-resistivity and groundwater geochemical data shows that there is intrusion salt water distribution area which occur in Trimulyo area with the resistivity value of 0,27 Ωm as the indicator of salinity and groundwater quality value parameters which show the salinity value of 3.600 mg/L, electrical conductivity of 6.370 μS/cm, dissolved oxygen of 0,8 ppm, and pH 7,7.